(untitled) (Journal of Technology and Operations Management, 2012)
The quest of university quality level is a never-ending journey, which is marked by searching a set of proper criteria. One of those criteria is the university’s teaching performance. The study aims toexplore the teaching performance through the application of Juran Trilogy in STML, UUM. Particularly the study is aim to gain a profound understanding of STML students’ satisfaction and how well the STML academicians able to satisfy the students’ need. Three managerial processes of the Juran Trilogy model was used for measuring education service quality. A total of 100 respondents were randomly selected. The questionnaire was distributed to the students in STML, UUM. The data analyzed through the SPSS package. The mean score and correlation being used to answer the research objectives. The results found that the overall of the educational quality is quite satisfied with the mean score is 3.57.The study also found that mean score of Planning was 3.57, Controlling was 3.53, and Improvement was 3.62. Therefore, STML academicians should apply controlling dimension in Juran Trilogy to increase the effectiveness of education quality. In conclusion, this study ableprovides a good overview about Juran Trilogy in terms of quality management towards student satisfaction. To be more reliable and realistic, the future research should have to consider enhance methods such as more respondent or mix-method.